PENGARUH BELANJA BARANG DAN JASA, DAN BELANJA MODAL TERHADAP EKUITAS DANA (Survei pada Satuan Kerja Perangkat Daerah Se-Kota Palu) - Nurhaeni, Nurhaeni (Katalogis, 2016)
This research aims to explore and determine the relationship between goods and services expenditures, capital expenditures,and equity funds. It also determines both simultaneous and partial impacts of goods and services, and capital expenditures on equity funds. Sample in this research consists of 33 governmental institutions in palu city, which is selected through purposive sampling technique, or selection based on ‘jugment’. The data analyzed quantitatively with multiple linear regressions analysis. The result indicates that equity funds decreased due to spending on good and service and capital during one accounting period. Simultaneous test shows that good and service, and capital expenditure have significant impact on equity funds in 33 govermental institutions. While partial test evidences that espenditures partially have significant impact on equity funds in 33 govermental institutions in palu. Coefficient determinant shows adjusted R-Square value of 0,782 that indicates that 78,20% of equity funds impacted by spending on goods and service, capital, while the remining of 21,80% is impacted by other variables that are not studied.